Tapping the green market: certification and management of non-timber forest products - Shanley, P.; Pierce, A.R.; Laird, S.A.; Guillen, A. (Routledge, 2002)
Non-timber forest products (NTFPs) are increasingly recognized as providing critical resources across the globe, fulfilling nutritional, medicinal, financial and cultural needs. However, NTFPs have largerly been overlooked in mainstream conservation and forestry politics. This book explains the use and importance of marked-based tools such as certification and eco-labelling for guaranteeing best management practices of NTFPs in the field. Using extensive case studies and global profiles of NTFPs, this book provides comprehensive understanding of certification processes and NTFPs management, harvesting and marketing. This practical volume includes valuable guidelines on NTFP management assessment and species-specific certification.